A case study of mergers and acquisition of the pharmaceutical industry in Vietnam and post-close performance - Ho, Thi Thu Van (2020)
When a company is expected to out-perform its market growth or the domestic market has become saturated and stagnant, company must look for growth opportunities abroad through globalization. Emerging markets which possess high economic potentials such as China, Russia, India are targeted by many large corporations around the world over the past decades. Some companies are also looking at the next in line markets which also possess high growth potentials but relatively higher risks to invest and benefit from these markets as first movers. However, while there are many researches were conducted on the emerging markets due to market attractiveness, there is very little researches conducted on emerging markets in waiting or frontier markets which made it harder for companies to navigate and be successful in these markets. This paper studies the market entry strategies of two well established international Pharmaceutical firms: “MA1” and “MA2” in Vietnam, the different M&A strategy adopted their post-acquisition performance.